The Early Childhood Workforce - DellaMattera, Julie (Maine Policy Review, 2009)
Julie DellaMattera describes how the strongest predictors of high-quality care and early education are the educational preparation of early educators, their continued training, compensation, and recognition of their professionalism. She presents information on the current patterns of educational preparation and poor compensation of early educators and offers recommendations to improve training and compensation. DellaMattera notes the need to also change public perceptions of those who work in the field of early care and education so that they are respected for their specialized knowledge.
Keywords: Maine; early childhood education; early childhood workforce